A review of injection and antibiotic use at primary health care (public and private) centers in Africa - Ofori-Asenso, Richard (J Pharm Bioallied Sci, 2015)
We conducted a review to study antibiotic and injections use at primary care centers (PHCs) within the World Health Organization African region. This was part of a larger study on prescribing indicators at PHCs within the region. We analyzed antibiotic and injection use reported in studies published between 1993 and June 2013, which were identified through searches conducted in PubMed, Scopus, Web of science, Africa-Wide NiPAD, Africa Journals Online, Google Scholar, and International Network for Rational Use of Drugs bibliography databases. Sub-group analysis was carried out for private and public centers. Data were retrieved from 18 studies in 6 countries involving 21,283 patient encounters across 338 PHCs. The percentage of patient encounters with antibiotics prescribed was 51.5% (IQR 41.1–63.3%). The percentage of patient encounters which resulted in the prescription of an injection was 36.8% (IQR 20.7–57.6%). Injection use rate at private facilities was 38% (IQR 19.1–42.7) while that of the public was 32.3% (IQR 20.6–57.6). Rate of antibiotic prescribing at public centers was 49.7% (IQR 51.1–75.7) and that of private facilities 57.6 (IQR 39.0–69.5). The percentage use of injections and antibiotics is high in Africa. The excessive use of antibiotics and injections are particularly more problematic in private than public facilities. Further research is needed to understand fully the underlying factors for the observed patterns and ways of improving medicines use.